Non-Profit Organizations in the Process of Integration with the European Community - Pozharevska, Rumiana (Research Papers, 2005)
There is no uniform view with regard to the nature and scope of the economic sector of nonprofit organizations, neither in countries with well-established practices and well-structured and grounded theory on not-for-profit organizations, nor in Bulgaria. The fact that there is more than a single term referring to the same economic agent, which has already proved its significance in the social and economic development of countries, poses a problem, the solution of which should not be postponed in the context of the European integration and the prospects of legal regulation of a non-profit legal entity. In comparing the critical analyses of Bulgarian and non-Bulgarian concepts, the author tries to define a notion encompassing all organizations functioning within Bulgaria, the ultimate goal of which is not to form a financial result, but to provide social assistance, or ‘cushion the blows’ of the developing free market economy, and raising the living standard.The large number of non-profit organizations set up in our country, the diversity of their articles of association and type of legal registration, the lack of any experience or bibliographical sources are objective difficulties, which non-profit organizations face in the EU accession process. Improving their performance will depend on how effectively they will cope with two key issues: defining and up-dating the mechanisms of raising finance, and the providing for an adequate accounting treatment and data presentation of their operations.